PERAN KEPALA DESA DALAM PENGEMBANGAN DESA WISATA (Studi Kasus Desa Wisata Sangeh, Kecamatan Abiansemal, Kabupaten Badung) - Dewi, Desak Made Trisna Juliantari (Jurnal Progress Administrasi Publik, 2024)
Tourism village development is the government's mission to improve community welfare through the development of productive businesses in the tourism sector in accordance with existing regional resources and potentials. The development of tourism villages requires the participation of village and community officials to support the progress of tourism villages. The participation of the village head is one of the important points in the development of tourism villages. This study aims to see and describe the role of the Village Head in the development of Sangeh Tourism Village. The method used will be a qualitative descriptive approach with data collection techniques through observation, interviews and documentation. The result obtained from this research is that the Head of Sangeh Village plays a role in becoming a bridge of cooperation between agencies and universities who want to provide coaching and training to the community. The village head and ranks also participated in the success of the Sangeh Festival which was used as a promotional event for Sangeh Tourism Village. The village head is also the initiator in making the mascot dance of Sangeh Village named "Sekar Pala". To maintain the integrity of the Sangeh Village area, the village head also participated in supporting the customary village policy not to trade and buy land ownership of Sangeh Village to investors. In addition, plans from the Badung Regency government and Sangeh Traditional Village in rearranging tourist attraction areas to make it easier for tourists to visit all tourist attractions in Sangeh Tourism Village. These development steps are expected to increase the existence of Sangeh Village as one of the tourist villages with its own uniqueness in Badung Regency.   Keywords: Role of Village Head; Tourism Village; Development